The Quest For The Origin Of John's Gospel : A Source-Oriented Approach - Brodie, Thomas L (New York : Oxford University Press, 1993)
Drawing on the insights of ancient literary theory and practice, this book seeks to unlock the age-old puzzle of the relationship of John's gospel to the other gospels and to the early Christian church. Applying a new method to an old problem, Brodie uses a form of source analysis that takes account of the practices of ancient writers to reveal John as someone who deliberately rendered the earlier gospels into a new language. The deeply theological, and at the same time more down-to-earth voice characteristic of John is revealed to be not that of a marginal community ("the Johannine community") but of an independent prophetic presence within the mainstream church. -- Publisher description
General Introduction: The Uncertain Quest and the Need for a Firmer Foundation -- The Uncertain Quest -- The Move from Specifics to a Broad Three-Part Inquiry -- The Quest for the Religious Background -- The Quest for the Purpose/Life-Situation -- The Quest for the History of a Johannine Community -- Towards Establishing a Partial Guide to History: John's Composition (Use of Sources) -- Composition as a Basis for History -- The Quest for Sources: The Central Problem -- The Thesis -- The Ancient Context: A World of Literary Transformation -- A Test Case: John 9 as a Dramatization of the Vision Theme in Mark 8:11-9:8 -- John's Systematic Use of All of Mark -- John's Systematic Use of Matthew -- John's Systematic Use of Part of Luke-Acts -- John's Systematic Use of the Pentateuch -- John's Systematic Use of Ephesians -- The Quest Resumed: Initial Conclusions -- The Religious Background -- The Purpose/Life-Situation -- Questions About the Reality of the Johannine Community: Towards Seeing the Evangelist as Primarily an Integrated Member of the Larger World-Oriented Christian Community or Church -- General Conclusion: From History to Spirit -- The Story of the Adulteress and the Accusers (John 7:53-8:11) -- John's Use of Names -- John's Use of the Pentateuch: A Tentative Outline of One Dimension -- John's Use of Part of Luke-Acts: A Tentative Outline of One Dimension -- John's Main Sources: An Approximate Summary
Includes bibliographical references (pages 177-185) and indexes
Keywords: Bible. -- Criticism, interpretation, etc; Christianity -- Scriptures